The Evolution of Ulul Albab Education in Malaysia: Development Framework and Implementation of tThe Andalusia 2.0 Conception Triangle Model - Noorsafuan Che Noh; Wan Zikri Qamaruddin; Zulkarnin Zakaria (RSIS International, 2026)
Indexed by ERA